First report of spot lesion of wheat caused by Pyrenophora teres f. sp maculata observed in Argentina. (August 2019) - Perelló, A.E.; Couretot, L.; Curti, A.; Uranga, J.P.; Consolo, V.F.
Abstract: Pyrenophora tritici-repentis, causal agent of tan spot, is the species commonly associated with leaf spotting symptoms on wheat ( Triticum aestivum L.) worldwide and in Argentina. On the other hand, P. teres is a major constraint on barley ( Hordeum vulgare L.) production, however the pathogen has not been reported in association with wheat crop in Argentina. In 2018, following a routine survey of wheat fields, leaves showing symptoms compatible with those caused by Pyrenophora spp. were observed in the principal wheat production areas in Buenos Aires and Entre Rios Provinces of Argentina. The disease incidence varied from 30% to 80%. Symptomatic wheat plants were collected from production fields and spotted foliar tissue with symptoms was plated onto PDA 2% growth medium. The isolates were tentatively identified as putative Pyrenophora spp. based on its colonies and conidia characteristics. Given the possibility of confusion by similar characteristics between some Pyrenophora species that infect wheat plants, the aim of this work was to clarify the identity of the fungus infecting this crop. In this study, we were able to confirm field observations in greenhouse assays on wheat plants using the fungal isolates. The seedling symptoms rate under artificial inoculation of five commercial wheat varieties was 100%. Pathogenicity tests and morphological studies as well as analyses indicated that the disease was caused by Pyrenophora teres . Molecular identification of the two isolates was doubled checked by PCR. First, the internal transcribed spacer (ITS) amplification and sequencing and specific PCR assay using PTT and PTM primers allowed to confirm that two monosporic isolates were P. teres f. maculata . This is a novel disease on wheat in Argentina caused by this pathogen. This finding is of great importance from the epidemiological point of view of the biodiversity of the fungus and also to contribute with the future management of the disease. Highlights: First report of the phytopathogenic Pyrenophora. teres f. maculata on wheat in Argentina. This study describes the isolation and identification of the fungus from wheat fields. Koch's postulates were fulfilled after fungal infection on wheat leaves.